Pengaruh Komitmen, Kepercayaan, dan Komunikasi Terhadap Kepuasan Pemasok Material di PT. Natura Plastindo Kecamatan Gempol Kabupaten Pasuruan - muhammad afif; Nur Dewi Rohmatus Sholihah (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This study aims to determine the effect of commitment, trust, and communication affect the satisfaction of material suppliers at PT. Natura Plastindo, Gempol District. This research is a type of quantitative research with hypothesis testing. The sample used in this study was 50 suppliers who contributed to PT. Natura Plastindo, Gempol District. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25 for windows. The primary data in this study were obtained from questionnaires whose measurements used a Likert scale and were tested for validity and reliability. The results of this study prove that commitment affects supplier satisfaction, trust affects supplier satisfaction, and communication also affects supplier satisfaction, besides commitment, trust, and communication simultaneously affect supplier satisfaction.Keywords: Commitment, Trust, Communication, and Supplier Satisfaction